Predictors of post prandial glucose level in diabetic elderly - Ni Putu Wulan Purnama Sari; Maria Manungkalit (Intelektual Pustaka Media Utama, 2019)
Post prandial glucose (PPG) level describes the speed of glucose absorption after 2 hours of macronutrient consumption. By knowing this, we could get the big picture of insulin regulation function and macronutrient metabolism in our body. In elderly, age-related slower glucose metabolism leads to diabetes mellitus (DM) in older age. This study aimed to analyze the predictors of PPG level in diabetics elderly which consist of functional status, self-care activity, sleep quality, and stress level. Cross-sectional study design was applied in this study. There were 45 diabetic elderly participated by filling in study instruments. Pearson and Spearman Rank correlation test were used in data analysis (α<.05). Results showed that most respondents were female elderly, 60-74 years old, had DM for 1-5 years with no family history, and only 33.33% respondents reported regular consumption of oral anti diabetes (OAD). Hypertension was found to be frequent comorbidity. Statistical analysis results showed that functional status, self-care activity, sleep quality, and stress level were not significantly correlated with PPG level in diabetic elderly (all p>α), therefore these variables could not be PPG level predictors. Other factors may play a more important role in predicting PPG level in diabetic elderly.